2022
DOI: 10.38211/joarps.2022.3.2.28
|View full text |Cite
|
Sign up to set email alerts
|

Considering Leaf Extract of Miracle Tree (Moringa Oleifera L.) and Potassium Nutrition for Contending Cotton Leaf Curl Virus (CLCuV) Disease of Cotton (Gossypium Hirsutum L.)

Abstract: Cotton leaf curl virus disease (CLCuV) is a devastating biotic factor that imposed crop productivity a huge loss. To battle this issue this study was assessed in 2019 for the evaluation of the response of leaf extract of miracle tree (Moringa oleifera L.) and potassium (K) nutrition to mitigate the plague of CLCuV disease in cotton variety CRIS-129. Treatments have consisted of the various K dosses Viz., 0, 100, and 150 kg K2SO4 ha-1, and 3% leaf extract of moringa was sprayed at 30, 60, and 90 days after emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…MLE being a rich source of growthpromoting hormones and nutrients showed its potential to a much greater range under traditional row spacing. Panhwar et al (2022) found that the use of the leaf extract of a miracle plant (Moringa oleifera L.) as a foliar spray on cotton, had significant effects on its yield and associated parameters. The highest boll weight and seed cotton yield were registered when foliar spray was done.…”
Section: Introductionmentioning
confidence: 99%
“…MLE being a rich source of growthpromoting hormones and nutrients showed its potential to a much greater range under traditional row spacing. Panhwar et al (2022) found that the use of the leaf extract of a miracle plant (Moringa oleifera L.) as a foliar spray on cotton, had significant effects on its yield and associated parameters. The highest boll weight and seed cotton yield were registered when foliar spray was done.…”
Section: Introductionmentioning
confidence: 99%
“…O K é essencial na ativação de enzimas que atuam nos processos de fotossíntese e respiração, bem como regulador osmótico necessário a manutenção do status hídrico da planta e regulação da abertura e fechamento estomático (RAWAT et al 2016, MOSTOFA et al 2022. Além disso, plantas adequadamente nutridas com K tendem a ser menos suscetíveis a doenças (DAVIS et al 2018, PANHWAR et al 2022. Por exemplo, em plantas de videira a severidade de oídio foi inversamente proporcional ao teor de K no pecíolo das folhas (PUSHPAVATHI et al 2020).…”
Section: Introductionunclassified